Distribution and Ecology of Decapod Crustaceans in Mediterranean Marine Caves: A Review - Carlo Nike Bianchi; Vasilis Gerovasileiou; Carla Morri; Carlo Froglia (Diversity, 2022)
Decapod crustaceans are important components of the fauna of marine caves worldwide, yet information on their ecology is still scarce. Mediterranean marine caves are perhaps the best known of the world and may offer paradigms to the students of marine cave decapods from other geographic regions. This review summarizes and updates the existing knowledge about the decapod fauna of Mediterranean marine caves on the basis of a dataset of 76 species from 133 caves in 13 Mediterranean countries. Most species were found occasionally, while 15 species were comparatively frequent (found in at least seven caves). They comprise cryptobiotic and bathyphilic species that only secondarily colonize caves (secondary stygobiosis). Little is known about the population biology of cave decapods, and quantitative data are virtually lacking. The knowledge on Mediterranean marine cave decapods is far from being complete. Future research should focus on filling regional gaps and on the decapod ecological role: getting out at night to feed and resting in caves during daytime, decapods may import organic matter to the cave ecosystem. Some decapod species occurring in caves are protected by law. Ecological interest and the need for conservation initiatives combine to claim for intensifying research on the decapod fauna of the Mediterranean Sea caves.